(untitled) (Global Journal of Medical Research, 2023)
Dental malocclusion is a highly prevalent pathology in domestic rabbits usually resulting from food management errors The present study aims to report the procedures used in a rabbit treated at the Veterinary Hospital in Jo o Pessoa Para ba affected by this pathology and to highlight the clinical characteristics and the treatment of occlusal adjustment made through tooth wear presented by this species in this condition